Angular Resolution for the Radio Neutrino Observatory Greenland (RNO-G) - Plaisier, Ilse; RNO-G Collaboration (SISSA, 2023)
In the ultra-high energy regime, the low predicted neutrino fluxes are out of reach for currently running neutrino detectors. Larger instrumented volumes are needed to probe these low fluxes. The Radio Neutrino Observatory Greenland (RNO-G) detects in-ice radio waves emitted by neutrino induced particle showers in the Greenlandic ice sheet. Radio waves have a large attenuation length in ice $\mathcal{O}$(1 km) and therefore RNO-G implements a sparse instrumentation to cover an unprecedented volume. The first seven RNO-G stations have been deployed in the summer of 2021 and 2022 and deployment will be ongoing in the next years.This contribution discusses the angular resolution of RNO-G. We use a method that uses a parametrization for the emitted electric field which is forward folded through the detector and matched with the voltage traces as obtained in the antennas of an RNO-G station. We obtain a $σ_{68%}$ angular resolution of 8$^°$ for an optimized event set (75$%$), and $σ_{68%}$=3$^°$ for the subset of events which have significant signal strength in two antennas measuring perpendicular electric-field components, such that a good measurement of the polarization can be obtained.